2015
DOI: 10.3109/13814788.2015.1109075
|View full text |Cite
|
Sign up to set email alerts
|

Six-year course and prognosis of traumatic knee symptoms in general practice: Cohort study

Abstract: KEY MESSAGESTraumatic knee symptoms in general practice seem to become a chronic disorder in one of three patients. Having knee symptoms at one-year follow-up is an important predictor of persistent symptoms at six-year follow-up. Several prognostic factors assessed at baseline are associated with persistent knee symptoms at one and sixyear follow-up. ABSTRACTBackground Traumatic knee symptoms are frequently seen, however, evidence about the course and prognostic factors are scarce. Objectives To describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Many studies have evaluated prognostic factors of the long-term clinical course of knee OA in general practice. These studies found that factors such as age, BMI, physical impairment measures and psychosocial factors hold prognostic value for knee OA (Alschuler et al, 2013;Belo et al, 2009;Holla et al, 2010Holla et al, , 2014Kastelein et al, 2016;Van Dijk et al, 2010). To date, only one CPR study from the knee OA literature sought to identify characteristics of people with knee OA who respond favourably to a specific treatment, in this case hip joint mobilization (Currier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated prognostic factors of the long-term clinical course of knee OA in general practice. These studies found that factors such as age, BMI, physical impairment measures and psychosocial factors hold prognostic value for knee OA (Alschuler et al, 2013;Belo et al, 2009;Holla et al, 2010Holla et al, , 2014Kastelein et al, 2016;Van Dijk et al, 2010). To date, only one CPR study from the knee OA literature sought to identify characteristics of people with knee OA who respond favourably to a specific treatment, in this case hip joint mobilization (Currier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Collection of outcome measures ranged from 54 months [ 26–28 ] to 3 months [ 24 26 , 29 ]. Follow-up frequency ranged from five follow up time points in three studies [ 24 , 26 , 28 ], two in two studies [ 27 , 31 ] and one in the remaining three studies [ 25 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study reported on co-morbidities [ 24 ]. Knee symptoms and signs were investigated in all eight studies; frequently reported were knee pain level [ 24–31 ], Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain, stiffness and function questionnaire [ 24–27 ], duration of knee symptoms [ 25 , 26 , 29 , 31 ] presence of locking [ 25 , 27 , 28 , 30 ] and symptoms of giving way [ 25 , 27 , 28 , 30 ]. Physical examination factors were reported in five studies [ 25 26 , 28 , 30 ] and frequently included palpable warmth [ 24 26 ], presence of a joint effusion [ 26 , 28 , 29 ], and collateral ligament testing [ 25 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations